In vitro Culture of lateral buds and zygotic embryos of Date Palm trees (Phoenix dactylifera) Talis (CVs). (Sebha University Conference Proceedings, 2024)
The lateral buds and zygotic embryos of date palm (Phoenix dactylifera var Talus) were cultured on different concentrations of plant hormones (2,4-D, NAA, IAA, Kin, and adenine) and activated charcoal (AC). Results revealed that the best responses were recorded when using MS + 2,4-D (20 mg/l), MS + IAA (20 mg/l) + AC (3 g/l) as high amounts of white granular friable culture after 9 weeks. Small amounts of callus were formed after one week, then small branches were regenerated and reached 3 centimeters in length after four weeks, respectively. When they inoculated on MS+ 2,4-D(20mg/l+Ad(5mg/l) +AC(3g/l) callus was induced after 1 week and small globular buds were formed after 2 weeks. No observations were recorded in the other treatment cases. The growth of callus increased when subculture formed MS + IAA (20 mg/l) + AC (3 g/l) to MS + Adenine (5 mg/l) + AC (3 g/l) after a week. On the other hand, no responses were noticed in the other treatments. When zygotic embryos were cultured on MS + 2,4-D (0.5 mg/l) + BAP (0.5 mg/l), only an increase in their growth after 2 weeks and a change in their color in the case of another treatment.